2019
DOI: 10.1021/acsomega.9b02025
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment Framework To Support the Design of Biobased Rigid Polyurethane Foams

Abstract: A methodological framework implementing laboratory activities and life cycle assessment is presented and applied to determine which parameters should be considered to develop biobased rigid polyurethane foams for thermal insulation with improved environmental performances when compared to their fossil counterparts. The framework was applied to six partially biobased (produced from bio-based polyols obtained from azelaic acid and/or lignin) and one fossil-based formulations. A comprehensive set of impact assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 26 publications
3
32
0
Order By: Relevance
“…The results of the study proved the applicability of the proposed methodological framework. The key points of the original model proposed by Manzardo et al 14 allowed the identification of the optimum in correspondence with a partial replacement of the virgin polyol with the recycled one. In this regard, Figure S8 shows the results that would have been obtained by merely basing the comparison on the foam mass without considering the thermal insulation properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the study proved the applicability of the proposed methodological framework. The key points of the original model proposed by Manzardo et al 14 allowed the identification of the optimum in correspondence with a partial replacement of the virgin polyol with the recycled one. In this regard, Figure S8 shows the results that would have been obtained by merely basing the comparison on the foam mass without considering the thermal insulation properties.…”
Section: Resultsmentioning
confidence: 99%
“…25 The methodology is structured into four iterative phases: goal and scope definition, inventory analysis, impact assessment, and interpretation of results. In this study, the framework proposed by Manzardo et al 14 that integrates the LCA methodology for an assessment of potential environmental impacts of biobased PUR in the design and development phase is used as the ground for the development of the proposal related to the recycled PUR ( Figure 2 ). The key points of the original model proposed by Manzardo et al, 14 namely, the integration of laboratory activities directly into the LCA (in particular, the design of the experiment implemented in goal and scope definition) and the choice of a functional unit that takes into account the physical performances of the insulating material are considered valid in the methodological proposal of this research, while the following modifications are introduced ( Figure 2 ): The set of impact assessment categories is substituted according to the recent EN 15804 standard for the assessment of the environmental sustainability of construction products.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6-8, as the sum of the thermal energy required to heat the mixture to the boiling point of acetone and that needed to vaporize the distillate [20]. (6) where α: relative volatility of the solvents; Ta: boiling temperature of polyol (454 K); Tb: boiling temperature of acetone (300 K); (7) where: Rmin: minimum reflux ratio; XLD: target purity of distillate (1); XLF: molar fraction of acetone in feed (0.944); (8) where: mmix: mass of the reaction mixture (kg); ΔHvap: enthalpy of vaporization (acetone: 511 kJ/kg); mdist: mass of the liquid to be vaporized (kg); ηheat: efficiency of heating device (90%).…”
Section: Polyol Production (S2)mentioning
confidence: 99%
“…However, a limited number of studies considering the environmental performance of partially bio-based PU foam do exist so far. Manzardo et al [8] compared the environmental performance of six partially biobased formulations (by using biobased polyols obtained from azelaic acid and/or lignin) and one fossil-based. The results showed that formulations containing azelaic-acid derived polyol and lignin-based polyol had better than fossil counterpart for all the impact categories considered.…”
Section: Introductionmentioning
confidence: 99%